Memória científica e institucional: contribuições conceituais para a Unidade Multidisciplinar de Memória e Arquivo Histórico (UMMA) da UFSCar - Prado, Samanta (Universidade Federal de São Carlos, 2019)
The safeguarding of scientific memory has been an increasingly worked issue in several institutions, and has received a growing focus of interest in the context of Brazilian universities. This work has as general objective to reflect on the elements that can support the proposition of - or complementation of the definition of what can be characterized as - a scientific and institutional memory within the Federal Institutions of Higher Education (IFES), with a view to at the same time, contribute to the conceptual complementation and validation of the proposal for the creation of the Multidisciplinary Memory and Historical Archives Unit (UMMA), Federal University of São Carlos (UFSCar),created in 2017.The methodology adopted is an exploratory and descriptive one, based on a bibliographical and documentary approach. As theoretical foundations, we discuss: (1) the concepts of science, memory, scientific memory, with the theoretical contribution of authors such as Merton (2013), Kuhn (1994), Deleuze and Guattari, Morin (2005), Bergson (2010), Halbwachs (2006) and Le Goff (2003); (2) the areas of archivology, librarianship and museology, based on authors such as Araújo (2014), Ortega (2004), Otlet (1993), Litton (1975), Bellotto (2006) and Buckland (1991); and to understand (3) the specificity of a Memory Center in the university context, authors such as Camargo and Goulart (2015). As practical references, initiatives related to the safeguarding of scientific and institutional memory in a set of federal universities in the country are analyzed, as well as the project to consolidate the UMMA proposal at UFSCar. The research is expected to contribute to studies related to scientific and institutional memory in the context of UFSCar and in the university context in a broad way. As results we present some proposals elaborated in order to offer suggestions to complement the creation document of UMMA, as well as indicate possible paths for the future development of UMMA.
Scientific and institutional memory: conceptual contributions to the Multidisciplinary Memory and Historical Archives Unit (UMMA) of UFSCar
Keywords: Memória científica e institucional; UMMA; Universidade Federal de São Carlos; Scientific and institutional memory; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO